KNOWLEDGE AND ATTITUDE OF PREGNANT WOMEN REPORTING AT TERTIARY CARE HOSPITAL - Sultana, Nighat; Fatima, Sadia; Muzaffar, Tabassum; Akram, Fahd (Pakistan Armed Forces Medical Journal, 2020)
Objective: To explore the knowledge and attitude of the pregnant women towards vaginal and caesarean delivery and association of socio-demographic factors with the knowledge and attitudes of the participants.Study Design: Cross sectional analytical study.Place and Duration of Study: Antenatal Clinic of Obstetrics and Gynaecology Department at a tertiary care hospital in Rawalpindi by self - administered interviews, from May 2018 to Oct 2018.Methodology: Three hundred and thirty-four women who attended antenatal clinic during the study period were interviewed using non-probability consecutive sampling method. The responses for chosen preferences were recorded on structured questionnaire after taking informed consent. All data was analysed using SPSS v.22.Results: The mean age of the women was 27.25 ± 4.235 years. Majority 291 (87.1%) of women interviewed had received formal education. Two hundred and thirty-two (69.5%) were unemployed and primigravida were111 (33.2%). The overall knowledge was found to be adequate in 204 (61.1%) participants for vaginal and in 149(44.6%) for caesarean section respectively. Two hundred and sixty seven (79.9%) of participants were willing for primary caesarean section but only 147 (44%) for elective repeat caesarean delivery. Only educational status (pvalue